The Dynamics of Women’s Empowerment as a Real-life Alternative Project for Women’s Engagement in the Traditional Coffee Industry : - Helmatun Fauza Ulfah; Khairatunnisa Khairatunnisa (Universitas Islam Negeri Antasari Banjarmasin, 2023)
This study aims to explore the role of women in traditional coffee factories in remote areas of Indonesia. It employs the Power and representation analysis, phenomenological research, and “Representing Other” approach in Travel Literature to examine how people use a universal structure or essence to understand their experiences. It highlights the significance of women's involvement in the coffee industry, particularly those who have long been part of the field. The research specifically examines the contribution of women to the world of traditional coffee factories, using a case study of